Determinants of green consumption intention among university students: Evidence from Thanh Dong University, Vietnam - Duyen, Vu Thi Mai; Thanh, Le Chi; Anh, Le Ngoc; Ngoc, Ha Bich; Hau, Vu Thi (Edelweiss Applied Science and Technology, 2025)
This study investigates the determinants influencing green consumption intention among university students in Vietnam, using Thanh Dong University as a representative case. The research aims to understand how cognitive, attitudinal, and environmental factors shape students’ willingness to adopt sustainable consumption behaviors. A quantitative research design was employed, with 300 valid survey responses collected from students across various academic disciplines. The measurement scales were validated using Cronbach’s Alpha and Exploratory Factor Analysis (EFA), followed by multiple linear regression to assess the effects of independent variables on green consumption intention. The findings reveal five significant predictors of students’ green consumption intention: (1) Green Consumption Knowledge, (2) Green Trust, (3) Health Awareness, (4) Price Perception, and (5) Environmental Awareness. Among these, Green Trust and Knowledge exert the strongest influence. The study concludes that enhancing students’ awareness, trust, and understanding of environmental issues can substantially promote sustainable consumption behavior. Managerial implications are proposed for universities and businesses to foster green values, integrate environmental education, and encourage responsible purchasing behavior among young consumers.